SISTEM PENGISIAN TANDON AIR GUNA PENYIRAMAN TANAMAN SECARA OTOMATIS MELALUI SMS GATEWAY - Santosa, Gatot (IST AKPRIND YOGYAKARTA, 2017)
Agricultural sector is playing vital role in Indonesia economy, in which irrigation mechanism is of key concern. Water management have to do optimally, both of suitability of water distribution, supply water and saving water and electricity. These problems can be overcome by designing a water level system for irrigation the plants by using a microcontroller Arduino Uno R3 and SMS Gateway. The water level control system consists of a main control that uses microcontroller Arduino Uno R3 which will take the data sent by resitif sensors, temperature sensors and moisture soil sensors and then compare it with the correct values and the results will be sent via SMS using the GSM TC35i. As for output used of water pumps, solenoid valve and the value of the moistuse soil and temperature sensors. From the test results are analyzed it can be concluded that the test was obtained power supply circuit output value of 13.6V DC. Testing the voltage divider circuit is divided into 3 output is 12V DC for the driver circuit, 9V DC to arduino, and 5V DC for TC35i. In the water reservoir when the height of 6.5cm below the resistance ranges from 200 to 400Î© and its output voltage reaches 0.3V. Error data on the LM35 temperature sensor of 0.2265625. For moisture soil sensors every 1% increase in soil moisture, the output voltage of 0,313V. In the test results of sending and receiving SMS takes time under 10 seconds